Transferências intergovernamentais aos municípios cearenses: efeitos sobre a composição e qualidade do gasto - Barbosa, Kelly Cristina de Oliveira (2013)
This paper analyzes the effects of intergovernmental transfers to the State of Ceará in 2010, which will be investigated through the proposal developed by Cossio (2002). We intend to demonstrate through an econometric model the effect of financing public spending through transfers in the composition of public expenditure by municipalities expense category (Bureaucratic, Social or Infrastructure) and check the quality of public spending. In particular, it was shown that intergovernmental transfers to municipalities increasing their overhead expenses and have a negative effect on their spending on infrastructure and the quality score of expense, and a statistically insignificant effect on social spending.